Evisceration With Implant Placement Posterior to Posterior Sclera. Issue 3 (May 2016) - Jordan, David R.; Stoica, Bazil
Abstract : Purpose: To describe the results and potential benefit of placement of a porous orbital implant (aluminum oxide) posterior to posterior sclera and compare the exposure rate with a former evisceration technique involving a posterior sclerotomy with placement of a porous implant partly within the scleral shell and partly within the intraconal space. Methods: Single-center, retrospective, interventional case series. A chart review of 93 patients undergoing evisceration with placement of an aluminum oxide orbital implant in conjunction with 2 different posterior sclerotomy techniques between 1999 and 2013 was carried out. Seventy-one patients met the inclusion criteria having 1 of 2 posterior sclerotomy techniques with an aluminum oxide orbital implant, a normal or near normal size eye and at least 6 months follow-up. Retrospective data analysis included demographic profile and treatment outcomes of the different posterior sclerotomy techniques. This study was performed with Institutional Review Board Approval and in compliance with the Declaration of Helsinki. Results: Thirty patients underwent the posterior radial sclerotomy technique, while 41 patients underwent implant placement posterior to posterior sclera technique. The average size implant used in the posterior radial sclerotomy technique was 18 mm versus 20 mm in the implant placement posterior to posterior sclera technique ( p < 0.001) with the implant placed posterior to posterior sclera. The exposure rate with the posterior radial sclerotomy technique was 5 of the 30 patients (16.7%) and 0 of 41 (0%) for the implant placement posterior to posterior sclera technique ( p = 0.006). Conclusion: Placement of an aluminum oxide orbital implant posterior to posterior sclera allowed the placement of larger implants which allowed enhancement of socket volume. In addition, it appeared to have a decreased risk of implant exposure during the study period. Porous implant placement posterior to posterior sclera is an alternate posterior sclerotomy technique that allows coverage of the implant surface with 3 layers of autogenous sclera. Abstract : Placement of an aluminum oxide orbital implant posterior to posterior sclera during evisceration surgery allowed a larger implant to be used and appeared to have a lower exposure rate during the study period compared to an earlier technique where the implant was more anterior.